Ludwik Fleck: a Philosopher Forgotten in Ukraine - Shepetiak, Oleh; Shepetiak, Оksana (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2020)
Ludwik Fleck is a philosopher, biologist and physician who had a decisive influence on Thomas Kuhn. The research is dedicated to a publication of the Ukrainian translation of the Fleck’smain work “Genesis and Development of a Scientific Fact” by Stefania Ptashnyk. The article deals with the scientific formation of Fleck, describes what happened to his philosophical achievements after his death and the outbreak of his popularity. The article presents the content of all Fleck’s works on philosophy, which are divided into three periods: preparatory, major and post-war. The main emphasis is on the formation of the key concepts of Fleck’s philosophy: “thought style” and “thought collective”.